Influence of Chlorella vulgaris Microalgae on the Performance of Membrane Bioreactors for Industrial Wastewater Treatment - Raygita May Hastuti; Hanan; Zuhriah Mumtazah; Helda Wika Amini; Meta Fitri Rizkiana (JOBC, 2023)
This research evaluated the Effect of Hydraulic Residence Time and Organic Loading Rate in a Microalgal Membrane Bioreactor for Wastewater Treatment. One method of treating industrial wastewater combines an anoxic procedure with a Moving Bed Biofilm Reactor (MBBR). In this study, process engineering is combined with microalgae to boost dissolved oxygen levels and counteract the rise in sludge. This study combines process engineering with microalgae to mitigate growing sludge and enhance wastewater quality as measured by dissolved oxygen levels. MLSS 1000 mg/L, Chlorella vulgaris microalgae 106 L, and 1.75 kg of urea and TSP were the microalgae concentrations utilized. The quality of industrial wastewater is positively impacted by adding microalgae in the MBBR process. The quality of industrial wastewater is positively affected by adding microalgae in the MBBR process. Adding microalgae caused the dissolved oxygen level to rise over the minimal threshold. Additionally, when wastewater is being treated, microalgae might lessen the chance of increasing sludge in the MBBR.